Effects and Moderators of Exercise on Sarcopenic Components in Sarcopenic Elderly: A Systematic Review and Meta-Analysis - Zhang, Yanjie; Zou, Liye; Chen, Si-Tong; Bae, Jun Hyun; Kim, Dae Young; Liu, Xiaolei; Song, Wook (Frontiers in Medicine, 2021)
Background: Sarcopenia refers to a muscle disease in loss of muscle strength, mass and function associated with aging. Although the protective effects of exercise on muscle mass and function are generally recognized, the relevant available findings in sarcopenic adults are controversial. It is necessary to conduct a systematic review to investigate the effects of exercise on muscle strength, body composition, and physical performance in older persons with sarcopenia, and to examine the potential moderators of demographic characteristics and exercise-related factors. Methods: Six databases (Medline, Embase, CINAHL, Scopus, Cochrane library and SPORTDiscus) were used to retrieve the eligible studies from inception to May, 2020. Two reviewers independently selected and extracted the data from each study, and effect sizes were calculated by employing random-effect models with 95% confidential interval (CI). The Physiotherapy Evidence Database (PEDro) scale was used to assess the study quality. Results: Seventeen studies (985 participants with sarcopenia, aged 67.6 to 86 years) were included in this review study. The meta-analytic results showed significant improvements in muscle strength (grip strength, SMD=0.30, 95% CI [0.15, 0.45], I2=6%, p<0.01; knee extension, SMD=0.32, 95% CI [0.15, 0.50], I2=0%, p<0.01; and chair and stand, SMD=0.56, 95% CI [0.30, 0.81], I2=36%, p<0.01), in physical performance (Timed up and go, SMD=0.74, 95% CI [0.48, 1.00], I2=0%, p<0.01; and gait speed, SMD=0.59, 95% CI [0.35, 0.82], I2=62%, p<0.01), and in body composition (Skeletal muscle mass index, SMD=0.37, 95% CI [0.15, 0.58], I2=16%, p<0.01; and Appendicular Skeletal Muscle, SMD=0.31, 95% CI [0.13, 0.49], I2=20%, p<0.01). However, there were no significant differences on other body composition (SMD=0.20-0.36). Additionally, meta-regression revealed that the higher percent of female participants was significantly associated with improved gait speed (β = 0.0096, p = 0.03) and decreased skeletal muscle mass index (β = -0.0092, p = 0.01). Conclusions: The findings from current meta-analysis suggested that exercise as a beneficial therapy had positively beneficial effects for older adults with sarcopenia. Some beneficial effects may be moderated by gender and exercise intensity.